Board Gender Diversity, Firm Performance and Risk-Taking: The Case of Non-Financial Firms of Pakistan - Mumtaz, Raheel; Rehan, Muhammad Farooq; Khan, Quaisar Ijaz; Zaidi, Rubab (iRASD Journal of Economics, 2021)
This paper examines the influence of board gender diversity on firm performance and risk taking. We employed the panel data of seventy-five non-financial firms of KSE-100 index listed in the Pakistan Stock Exchange. The data consists of 2005-2018 period. Results of panel regression reveal that board gender diversity have adverse influence on the firm performance i-e Tobin’s Q and return on assets. Moreover, it further provides that board gender diversity has decrease the firm’s risk-taking i-e insolvency risk. Overall, the inclusion of females in the boardroom reduces the financial performance and decrease the risk-taking of non-financial firms in Pakistan. This study provides the managerial and practical implications in compliance with SECP Act of 2017, to include the females in boardroom to discourage the risk-taking behavior of firms.